THE RELATIONSHIP BETWEEN ORTHODONTIC TREATMENT AND PERIODONTAL HEALTH - HALIM, HIMAWAN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
There is a need to consider numerous factors in orthodontic treatment, including diagnosis before and during treatment. This activity is necessary to prevent the incidence of periodontal abnormalities or the aggravation of existing ones, which is possibly overcome through orthodontic treatment under certain circumstances.